THE CONTENT OF FOREIGN LANGUAGE TRAINING FOR NON-LINGUISTIC STUDENTS IN HIGHER EDUCATION IN THE CONTEXT OF CONTEMPORARY CHALLENGES - Nataliia Bespalova; Neliia Blynova; Svitlana Medynska; Anna Voloboieva (Alfred Nobel University Journal of Pedagogy and Psychology, 2025)
This article addresses current issues in the theory and practice of teaching General English, Business English and English for Professional Purposes. These academic disciplines are based on the study of core lex- ical and grammatical material, as well as specialized terminology, aimed at equipping students of non-lin- guistic majors with the necessary language competencies for future professional use. The purpose of this article is to systematize a range of issues and challenges faced by instructors when developing course syllabi, and to offer practical recommendations based on the experience of the De- partment of Foreign Languages in designing educational and methodological frameworks for such disci- plines as Foreign Language, Foreign Language for Business and Foreign Language for Professional Purpos- es targeted at students of non-linguistic specialties. Methodology. The analysis of relevant academic sources helped assess the current state of research on the topic and identify the main directions of domestic and international studies in the field of teaching General English, Business English and English for Professional Purposes. The descriptive method enabled the generalization of findings collected during the research process, while the synthesis of the obtained data contributed to the development and implementation of the study’s conceptual framework. The main types of student learning activities, as defined by the curriculum, include the study of ba- sic terminology through the analysis of both original and adapted English-language texts; the development of reading, comprehension, and translation skills; and the enhancement of communicative competencies within the scope of professionally relevant topics. The authors examine current teaching approaches and the stages of skill formation in this context. The primary objective of instruction is to develop learners’ competencies in professional communica- tion, the ability to access up-to-date specialized information from both domestic and international sources, to deliver presentations on professional topics and on the results of their own research, within a framework defined by their occupational needs. Training also aims to prepare students to address professional tasks, solve job-related situations, and manage potential challenges in their future careers. To improve the quality of higher education and foster learners’ engagement, active teaching meth- ods have been integrated into the educational process. Faculty members have employed a variety of in- structional techniques, including role-plays, business and simulation games, project-based learning (in both group and individual formats), case study method, student presentations, discussions, facilitation and col- laborative learning techniques, debates, online research, speaking clubs and workshops with business pro- fessionals. The paper outlines the requirements for designing curricula and textbooks, systematizes the key is- sues faced by instructors in developing syllabi, and provides practical recommendations for the creation of educational and methodological complexes for such academic courses as Foreign Language, Foreign Lan- guage for Business and Foreign Language for Professional Purposes tailored to students of non-linguistic majors. Conclusions. Thus, the development and implementation of educational programs by the department consider the specific characteristics of both domestic and international labour markets, as well as the needs and demands of students. Instruction is supported by a structurally logical sequence of disciplines, ensuring continuity with the content acquired in previously studied courses.